1993
DOI: 10.1128/jcm.31.6.1562-1569.1993
|View full text |Cite
|
Sign up to set email alerts
|

Detection, typing, and subtyping of enteric adenoviruses 40 and 41 from fecal samples and observation of changing incidences of infections with these types and subtypes

Abstract: Monoclonal antibody (MAb) preparations specific for the enteric adenoviruses of subgenus F (AdF) were generated and evaluated as typing reagents in virus neutralization tests and enzyme-linked immunosorbent assays (ELISAs). A panel of 11 genome types of adenovirus 40 (Ad40), 24 genome types of Ad4l, and 47 adenovirus prototype strains was used to determine the specificities of the MAbs in the two assays. In this way two MAbs, MAb 40-1 (anti-Ad40) and MAb 41-1 (anti-Ad4l) were selected. These two MAbs showed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
25
1
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 41 publications
8
25
1
3
Order By: Relevance
“…Enteric adenoviruses types 40141 were detected by Adenoclone EIA in 4.5% of the patients with diarrhea and in one child in the control group (1.3%). Similar detection rates have been reported by others [Kidd et al, 1986;Herrmann et al, 1988;Shinozaki et al, 1988;Jarecki-Khan et al, 1993;de Jong et al, 1993;Leite et al, 1985;Niel et al, 1986;Mistchenko et al, 19921. The etiological relationship of adenovirus and diarrhea was supported by the exclusion of other causative microorganisms and toxins [Stewien et al, 19931 except in one case with dual infection with astrovirus and especially for the enteric adenoviruses (Ad 40141) by significant difference in detection rates in diarrhea and in the controls.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Enteric adenoviruses types 40141 were detected by Adenoclone EIA in 4.5% of the patients with diarrhea and in one child in the control group (1.3%). Similar detection rates have been reported by others [Kidd et al, 1986;Herrmann et al, 1988;Shinozaki et al, 1988;Jarecki-Khan et al, 1993;de Jong et al, 1993;Leite et al, 1985;Niel et al, 1986;Mistchenko et al, 19921. The etiological relationship of adenovirus and diarrhea was supported by the exclusion of other causative microorganisms and toxins [Stewien et al, 19931 except in one case with dual infection with astrovirus and especially for the enteric adenoviruses (Ad 40141) by significant difference in detection rates in diarrhea and in the controls.…”
Section: Discussionsupporting
confidence: 91%
“…Since Ad40 grows poorly even in HEK-293 cells, which are considered permissive [Brown et al, 1984;Brown, 19851, and some workers failed to cultivate it in these cells [Brown et al, 1984;Niel et al, 19861, this sample may be considered as Ad40. Lower ratios of Ad40 in gastroenteritis have been observed to be widespread geographically [de Jong et al, 1993;Shinozaki et al, 19881. Ad40 was detected in Brazil in samples collected among 1981 and1985 in Rio de Janeiro [Niel et al, 19861, but not cultivated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys on the circulating adenovirus types have shown a change in the dominant types. Studies carried out between 1981 and 1989 in the Netherlands [de Jong et al, 1993], and 1987in Bangladesh [Jarecki-Khan et al, 1993, have shown a decrease in the incidence of Ad40 infections, resulting in Ad41 becoming the dominant type [Noel et al, 1992;Jarecki-Khan et al, 1993;de Jong et al, 1993]. It has been suggested that this increased prevalence of Ad41 may be due to the occurrence of antigenic drift, thus resulting in an increase in the incidence of infection in susceptible individuals [Crawford-Miksza and Schnurr, 1996a,b].…”
Section: Introductionmentioning
confidence: 99%
“…Fifty-one human adenovirus serotypes have been distinguished on the basis of their resistance to neutralization by antisera to other known adenovirus serotypes. The various serotypes are classified into six subgenera from A to F based on their hemagglutination reaction with human and animal erythrocytes (10,12,15,27). Epidemiological studies performed in various industrialized countries demonstrated that EAd ranked only second in the etiology of viral gastroenteritis in infants and young children and its positive rate of infection in sporadic cases and outbreaks of acute gastroenteritis ranged from 1.1% to 12.0% (2,6,29).…”
mentioning
confidence: 99%